Osthole Alleviates Neointimal Hyperplasia in Balloon-Induced Arterial Wall Injury by Suppressing Vascular Smooth Muscle Cell Proliferation and Downregulating Cyclin D1/CDK4 and Cyclin E1/CDK2 Expression - Li, Yi-Qi; Li, Ye-Li; Li, Xiao-Tong; Lv, Jun-Yuan; Gao, Yang; Li, Wen-Na; Gong, Qi-Hai; Yang, Dan-Li (Frontiers in Physiology, 2021)
Abstract: Percutaneous coronary intervention (PCI) is the most widely used therapy for treating ischemic heart disease. However, intimal hyperplasia and restenosis usually occur within months after angioplasty. Modern pharmacological researchers have proven that osthole, the major active coumarin of Cnidium monnieri (L.) Cusson, exerts potent antiproliferative effects in lung cancer cells, the human laryngeal cancer cell line RK33 and TE671 medulloblastoma cells and that its mechanism of action is related to cell cycle arrest. The goal of the present study was to observe the effect of osthole on VSMC proliferation using PDGF-BB-stimulated VSMCs isolated from rats and vascular balloon injury as models to further elucidate the molecular mechanisms underlying this activity. We detected the relative number of VSMCs by the MTT assay and EdU staining and examined cell cycle progression by flow cytometry. To more deeply probe the mechanisms, the protein expression levels of PCNA, the cyclin D1/CDK4 complex and the cyclin E1/CDK2 complex in balloon-treated rat carotid arteries and the mRNA and protein expression levels of the cyclin D1/CDK4 and cyclin E1/CDK2 complexes in VSMCs were detected by real-time RT-PCR and western blotting. The data showed that osthole significantly inhibited the proliferation of VSMCs induced by PDGF-BB. Furthermore, osthole caused apparent VSMC cell cycle arrest early in G0/G1 phase and decreased the expression of cyclin D1/CDK4 and cyclin E1/CDK2. Our results demonstrate that osthole can significantly inhibit PDGF-BB-induced VSMC proliferation and that its regulatory effects on cell cycle progression and proliferation may be related to the downregulation of cyclin D1/CDK4 and cyclin E1/CDK2 expression as well as the prevention of cell cycle progression from G0/G1 phase to S phase. The abovementioned mechanism may be responsible for the alleviation of neointimal hyperplasia in balloon-induced arterial wall injury by osthole.